Pengaruh Tiktok Terhadap Trend Fashion Pada Mahasiswa di Mojokerto - Fatikh, M. Alfin; Fajri Irwan Muhammad (Bahasa Indonesia, 2024)
The TikTok App is a video-based social media that provides special effects features released in 2016. Over the last few years, Tiktok App has significantly developed so that this has been a major opportunity for everyone to become creative utilizing TikTok App with a variety of content, one of which is content around the fashion world. The presence of various content about fashion trends has become a pleasure for the audience, especially for students who follow the current developments of the fashion world, where the TikTok App has rapidly become a reference in student dress styles to follow the latest trends. This research applies descriptive quantitative research that uses a survey method with the Cluster Rendom Sampling technique, In obtaining data using the Slovin formula technique where 94 respondents were found. Furthermore, data analysis using simple linear regression analysis to determine the magnitude of the influence caused by the influence of social media TikTok on fashion trends in students. Accordance the output of this study, shows that there is a significant influence between the use of the TikTok App on fashion trends towards students with a correlation of 0.608 and a coefficient of determination of 0.369, which means that the effect of social media on TikTok on fashion trends in students is 36.9%.